2017
DOI: 10.1038/s41598-017-14738-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of wild and cultivated Amorphophallus paeoniifolius populations in southwestern China as revealed by RAD-seq

Abstract: Amorphophallus paeoniifolius, is a commercially important vegetable crop because of its high production potential. In this study, we generated a total of 166 Gb of genomic data from 16 wild and 20 cultivated A. paeoniifolius individuals in southwestern China using restriction site associated DNA sequencing (RAD-seq). We compared the genome-wide variations between the wild and cultivated populations. Wild populations exhibited higher genetic diversity than did cultivated populations based on private allele numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 44 publications
5
29
0
Order By: Relevance
“…The total number of alleles obtained for V. floribundum in this study is similar to those reported for wild V. angustifolium and V. corymbosum clones [35], and higher compared to those reported for V. macrocarpon cultivars [64]. Several studies report that intensive selection and inbreeding during domestication processes reduce the genetic diversity in many plant species and increase genetic drift [65,66], which could explain why wild Vaccinium species are more diverse than their domesticated counterparts. The global expected heterozygosity (He) in this study is similar to the He reported for V. sieboldii (H E =0.73) and V. ciliatum (H E =0.75), both wild endangered species [67].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The total number of alleles obtained for V. floribundum in this study is similar to those reported for wild V. angustifolium and V. corymbosum clones [35], and higher compared to those reported for V. macrocarpon cultivars [64]. Several studies report that intensive selection and inbreeding during domestication processes reduce the genetic diversity in many plant species and increase genetic drift [65,66], which could explain why wild Vaccinium species are more diverse than their domesticated counterparts. The global expected heterozygosity (He) in this study is similar to the He reported for V. sieboldii (H E =0.73) and V. ciliatum (H E =0.75), both wild endangered species [67].…”
Section: Discussionsupporting
confidence: 83%
“…The global expected heterozygosity (He) in this study is similar to the He reported for V. sieboldii (H E =0.73) and V. ciliatum (H E =0.75), both wild endangered species [67]. A high level of genetic diversity in these species could indicate random mating among individuals, a common feature of wild plant species [6667].…”
Section: Discussionsupporting
confidence: 83%
“…The most likely route is starting at Turkmenistan, passing successively through the south coast of the Aral Sea, today's Kazakhstan, Kyrgyzstan, the north and south of the Tianshan Mountains into the northern Xinjiang, and then getting to the Hexi corridor (Zhang & Luo, 2014). In addition, most experts have devoted themselves to the study of genomic DNA of Bactrian camels using microsatellites to reveal the genetic evolution of Bactrian camels distributed in different regions, providing basic research materials for the protection and utilization of Bactrian camels (Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In genetics, PCA mainly converts multiple differences into a few independent factors and analyzes the differences among different groups by the degree of difference among these factors to classify different populations (Gao et al, 2017). In this study, after removing the site with a deletion rate of 50% or more, the remaining 865,774 loci were used for the calculation of PCA.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…paeoniifolius has long been used as a local staple food in many countries such as the Philippines, Indonesia, Malaysia, Bangladesh, India, China and other Southeastern Asian countries (Sugiyama and Santosa 2008). It is an important economic crop because of its high production potential (50-60 t/ha) and is usually used as vegetable (Gao et al 2017), and its tubers are rich in nutrients. It is a healthy low-fat food, containing a good source of protein as well as starch (Bais and Mali 2013).…”
Section: Potential Of Suweg and Other Herbsmentioning
confidence: 99%